Treg stability: to be or not to be. (April 2016) - Overacre, Abigail E; Vignali, Dario AA
Highlights: Treg stability remains a controversial topic and thus requires further study. Tregs can lose suppressive function while maintaining Foxp3 expression. Treg stability maintained in part by epigenetic modifications, FOXO, Eos and Nrp1. Treg stability may be therapeutically manipulated to treat cancer and autoimmunity. Abstract : Regulatory T cell (Treg ) stability has been primarily determined by the maintained expression of the transcription factor Forkhead box P3 ( Foxp3 ). However, Tregs can exhibit instability while maintaining Foxp3 expression, requiring a re-examination of what defines Treg stability. Recent work suggests that the establishment and stability of Tregs is mediated by a number of mechanisms besides Foxp3 expression, such as epigenetic modifications, Foxo1/3a localization, expression of Eos and signaling via Neuropilin-1. Additional studies may help to define approaches that can undermine Treg stability in cancer or enhance Treg stability in transplantation, autoimmune or inflammatory diseases and therefore have substantial therapeutic utility. In this review, we will discuss how Treg stability is defined and the mechanisms utilized to maintain stability.